2014
DOI: 10.1111/aos.12408
|View full text |Cite
|
Sign up to set email alerts
|

Circadian intraocular pressure patterns in healthy subjects, primary open angle and normal tension glaucoma patients with a contact lens sensor

Abstract: ABSTRACT.Purpose: To examine the circadian intraocular pressure (IOP) patterns in healthy subjects, in primary open angle and normal tension glaucoma (POAG; NTG) using a contact lens sensor (CLS; Sensimed Triggerfish, Lausanne, Switzerland). Methods: This was an observational, nonrandomized study. Ten healthy subjects (Group 1, 10 eyes) and 20 glaucomatous patients [20 eyes, 10 with POAG (Group 2) and 10 with NTG (Group 3)] were enrolled. All patients were controlled with prostaglandin analogues. The 24-hr IOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 48 publications
10
93
0
2
Order By: Relevance
“…Recently, 24 h IOP monitoring has received attention in an attempt to characterise the dynamic changes of IOP especially during sleep 23 24. Mansouri and Shaarawy23 studied patients with glaucoma progression despite normal IOPs during clinic hours who underwent ‘24 h IOP monitoring’ with the contact lens sensor, and found that the peak ‘IOP’ occurred in 69% of patients during the nocturnal/sleep period.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 24 h IOP monitoring has received attention in an attempt to characterise the dynamic changes of IOP especially during sleep 23 24. Mansouri and Shaarawy23 studied patients with glaucoma progression despite normal IOPs during clinic hours who underwent ‘24 h IOP monitoring’ with the contact lens sensor, and found that the peak ‘IOP’ occurred in 69% of patients during the nocturnal/sleep period.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a wireless contact lens sensor (CLS, Triggerfish; Sensimed, Lausanne, Switzerland) has been developed for monitoring 24-hour IOP at home without the need of awakening subjects during sleep [10], [11]. Several reports have demonstrated good tolerability of the CLS for 24-hour recordings, but the clinical applications of the CLS need to be investigated [12]-[19]. By design, the CLS detects the circumferential change in the corneoscleral curvature that is under the influence of IOP.…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma patients do not follow this circadian pattern and have more IOP variability. 13 In conclusion, the corneal deformation response to an air puff is dependent on IOP and pachymetry and not only on the biomechanical properties of the cornea. Therefore, this deformation by itself cannot be considered a parameter that accurately characterizes the biomechanical behavior of a specific cornea.…”
Section: Discussionmentioning
confidence: 89%
“…This agrees with results in studies of IOP variability in the circadian cycle in healthy subjects. 13 However, a larger number of patients is required to confirm this observation. In addition, the study should consider different types of corneas, not only healthy ones.…”
Section: Discussionmentioning
confidence: 94%